If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying M + 7 = -22 Reorder the terms: 7 + M = -22 Solving 7 + M = -22 Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + M = -22 + -7 Combine like terms: 7 + -7 = 0 0 + M = -22 + -7 M = -22 + -7 Combine like terms: -22 + -7 = -29 M = -29 Simplifying M = -29
| -5(r+4)=-79 | | 6a-2=8a | | Y=5+.8x | | h(6)=-1/2x-7 | | 4x+3(2x+6)-3-x=9x+15 | | 3B+6a=-12 | | P-1.5=8 | | -3(0.25+0.25y)+2y=-3 | | 9x-32=8x-8 | | 100-4Q=M | | 10(k-3)=-2k+12 | | y^2+8=3y(y-2) | | 15w+-2w+29=5w-27 | | Tanh(x)=x | | 18-8n=4n-6(7n+2) | | 5k-19=-5-19k | | 104=4(1+8x)-7x | | 9x(x)=30 | | 2x-.5y=6 | | 132.49s+15=192.49 | | 24+21x-9x=15x+6+24 | | 5x-3+2x-6+3x-2*5x+1-4x*3-5+6=1 | | 5/8(a-2)=10 | | 6x+7=82-13 | | 36+-10=8q | | 2-2(4x+3)=18-3x+3 | | 6-a=6(1+8a) | | 30=(3w-1)xw | | 6x-4*3+7x*2-5+2-6x*3=8x | | 8x-10x=12 | | 8*3=2*2+2x-2+2-67x+2 | | 4-2(-2)=5-(-2)+1 |